(untitled) (CIPEEX, 2022)
WITH THE OCCURRENCE OF THE COVID-19 PANDEMIC, WHICH TOOK THE LIVES OF SEVERAL PEOPLE ANDBROUGHT TO THE SURFACE SOCIAL, SANITARY, ECONOMIC AND ENVIRONMENTAL IMPACTS, NUMEROUSPROBLEMS FOR THE POPULATION WERE TRIGGERED. AMONGST THEM, A RESEARCH CONDUCTED BY THEBRAZILIAN MINISTRY OF HEALTH NOTED AN ALARMING DROP IN BLOOD DONATION RATES AND A LACK OF STOCKIN BLOOD DONATION FACILITIES. IN ADDITION, A PUBLICATION BY THE UNIVERSITY OF SÃO PAULO (USP) STATESTHAT STORING LEFTOVER MEDICATION IS A VERY COMMON HABIT AMONG BRAZILIANS AND, OVER TIME, WASOBSERVED A LARGE INCREASE IN EXPIRING DRUGS AND MEDICINE. THE PROJECT AIMS TO RESEARCH, PLANAND DEVELOP AN APPLICATION TO IMPROVE THE PROCESSES OF BLOOD AND DRUGS FOR LEUKEMIA TREATMENTDONATION. AIMING TO ENCOURAGE, INFORM AND RETAIN DONATION FREQUENCIES TO REACH HIGHER NUMBERSIN CONTRIBUTION RATES. VIA EXPLORATORY RESEARCHES, OBSERVATION, AND STUDIES DIRECTED TO THETHEMATIC AND WITH INTENTION OF FURTHER USE OF DATA COLLECTION AND HANDLING PRACTICES, WE SEEK ABETTER UNDERSTANDING OF THE PHENOMENA INVOLVING SUCH PROCESSES, GAINING KNOW-HOW ON THEREASONS FOR NON-DONORS AND INACTIVE DONORS. THUS, IMPLEMENTING POSSIBLE SOLUTIONS FORCONTRIBUTION GATHERING WITHIN THE APPLICATION. SO FAR, THE RESULTS ACHIEVED OBTAINED ELEVENARTIFACTS OF THE REAL PROJECT, PRODUCED FROM CONCLUSIONS DRAWN WITHIN THE RESEARCH, ACHIEVINGESTABLISHED MILESTONES OF THE PROJECT.